Critical Analysis of Strengthening the Character of Cooperation through Discussion Method in Social Science Learning in Karanggedang 03 State Elementary School - Eka Agus Purnomo (Green Publisher, 2024)
This study aims to analyze the strengthening of cooperation character through discussion methods in Social Science learning at the elementary school level. Social Science learning often employs discussion methods that require cooperation among students. However, the current state of student collaboration in these discussions is not optimal. Some students are reluctant to join and interact with their groups, do not take responsibility for completing tasks together, struggle to think critically to solve problems collaboratively, and are afraid to express their opinions in public. The purpose of this research is to determine the abilities, constraints, and solutions related to student cooperation in discussion methods. The research was conducted at SDN Karanggedang 03 in Cilacap Regency using a qualitative research method. Data collection techniques included interviews with teachers and students. The study's findings identified five indicators of student cooperation ability in discussion methods: social interaction (groups), responsibility, mutual help, critical thinking, and problem-solving. A notable obstacle during group discussions was the lack of active participation by a small number of students in completing group tasks, such as mutual aid activities. Proposed solutions include building cohesiveness, engaging in discussions with other members, and diligently carrying out tasks. Based on the analysis of these aspects, it can be concluded that the achievement of cooperation abilities in discussion methods is largely effective, though some areas still require improvement in the learning process.